From Tradition to Transformation: Reimagining Islamic Religious Education in the Digital Age - Mulyadi, Mulyadi (Universitas Islam Indonesia, 2025)
The transformation of Islamic Religious Education (IRE) in higher education has become an urgent need to face the challenges of the digital era characterized by rapid technological advancement, globalization, and value disruption. This study aims to analyze the forms, challenges, and implementation strategies of IRE transformation in universities. Using a qualitative descriptive method through a library research approach, this study finds that IRE transformation involves three main dimensions: (1) innovation in technology-based teaching methods, (2) curriculum renewal emphasizing competency and character development, and (3) enhancement of digital literacy among lecturers and students. The integration of technologies such as e-learning, social media, and digital learning platforms contributes to expanding access and improving the quality of religious education. However, challenges such as infrastructure inequality, limited digital literacy, and the potential erosion of spiritual values persist. Therefore, IRE transformation in higher education should combine technological innovation with the strengthening of spiritual, moral, and Islamic character values. Such an approach is essential to develop a generation of Muslim intellectuals who are both adaptive to change and rooted in moderate Islamic principles.